2022
DOI: 10.1371/journal.pone.0266250
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based dual affinity optimization of a SARS-CoV-1/2 cross-reactive single-domain antibody

Abstract: The SARS coronavirus 2 (SARS-CoV-2) spike (S) protein binding to the human ACE2 receptor is the molecular event that initiates viral entry into host cells and leads to infection and virus replication. There is a need for agents blocking viral entry into host cells that are cross-reactive with emerging virus variants. VHH-72 is an anti-SARS-CoV-1 single-domain antibody that also exhibits cross-specificity with SARS-CoV-2 but with decreased binding affinity. Here we applied a structure-based approach to affinity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
(50 reference statements)
1
8
0
Order By: Relevance
“…5). In agreement with previous reports, we found that VHH-72 bound >5x weaker to SARS-CoV-2 than to SARS-CoV-1 15,26 . Overall, 13 VHH sequences (Seqs 1-12 and VHH-72), showed high protein expression (>10 mg/L) in E. coli.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…5). In agreement with previous reports, we found that VHH-72 bound >5x weaker to SARS-CoV-2 than to SARS-CoV-1 15,26 . Overall, 13 VHH sequences (Seqs 1-12 and VHH-72), showed high protein expression (>10 mg/L) in E. coli.…”
Section: Resultssupporting
confidence: 93%
“…Overall 5,361/7,716 (69.5%) ML-designed sequences with up to 15 substitutions showing signi cant (p <= 0.05 Mann-Whitney U-test, Bonferroni correction) improvement over VHH-72 against SARS-CoV-2 WT, compared to 338/1496 (22.6%) baseline sequences with up to nine substitutions (Figure 2D, E, F). We note that previously reported VHH-72 variants with improved binding a nity that have up to 8 substitutions 15,25,26 . Overall these results provide evidence that the ML models extrapolate accurately to identify functional sequence variants with multiple mutations.…”
Section: Resultsmentioning
confidence: 66%
“…Pseudovirus neutralization assay was performed in 384-well plate format adapted from previously described protocol and modification 27 , 28 . Briefly, 4-fold serial dilutions of the serum samples were incubated with diluted virus at a 2:1 ratio for 1 h at 37 °C before addition to HEK293-ACE2/TMPRSS2 cells obtained from BEI Resources repository of ATCC and the NIH (NR-55293).…”
Section: Methodsmentioning
confidence: 99%
“…The increased binding capacity between the mutant antibodies and the RBD is mainly due to the increase in the electrostatic interactions and the free energy of solvation of the polar species. Additionally, using ADAPT (Assisted Design for Antibody and Protein Therapeutics), a platform that combines structure-based computational predictions with experimental testing, the binding affinity can be further optimized [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%